Meningkatkan Kemampuan Berbicara Bahasa Inggris Peserta Didik dengan Menggunakan Metode Window Shopping - Kurniawati, Rizki; Mufaridah, Fitrotul; Suharto, Suharto (Indonesian Journal Publisher, 2023)
Being proficient in English is a necessity in the modern and evolving era, involving the use of English in various aspects of life. Many children have already become proficient in understanding and reading in English, but their speaking abilities remain an unresolved issue. There are many factors that contribute to the lack of speaking proficiency in English, one of which is the limited opportunity to practice and a lack of confidence. In this article, the researcher conducted a classroom action research focusing on improving the speaking skills of students, particularly at the high school level. The researcher employed the window shopping or gallery walk method to assist students in honing their speaking abilities. Thirty-six students were divided into several groups, with 1-2 individuals as presenters and other group members serving as evaluators who would engage in gallery walk/window shopping with other groups, providing questions, opinions, and suggestions. The results of the researcher's observations during the presentations indicated an improvement in students' English speaking abilities from the first to the second cycle of implementation.